2011
DOI: 10.1002/iub.557
|View full text |Cite
|
Sign up to set email alerts
|

Signaling epigenetics: Novel insights on cell signaling and epigenetic regulation

Abstract: Cells must be able to respond rapidly and precisely not only to changes in their external environment but also to developmental and differentiation cues to determine when to divide, die, or acquire a particular cell fate. Signal transduction pathways are responsible for the integration and interpretation of most of such signals into specific transcriptional states. Those states are achieved by the modulation of chromatin structure that activates or represses transcription at particular loci. Although a large v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 115 publications
0
24
0
Order By: Relevance
“…It is becoming an accepted paradigm that an intimate and dynamic relationship exists between signaling mediators and the epigenetic machinery (42). Within this framework, eHsp90 is emerging as an effector of epigenetic cross-talk, linking ERK activation with EZH2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming an accepted paradigm that an intimate and dynamic relationship exists between signaling mediators and the epigenetic machinery (42). Within this framework, eHsp90 is emerging as an effector of epigenetic cross-talk, linking ERK activation with EZH2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although scarce, current pioneering studies have clearly shown the epigenetics-signal transduction crosstalk (Arzate-Mejıa et al 2011) and the role of signal transduction pathways in the maintenance of genetic variation by balancing selection (Penn and Siemens 2010). Recent reports in mammals describe a direct link between balancing selection and epigenetic variation (Arzate-Mejía et al 2011;Okhovat et al 2014;Renn and Siemens 2010).…”
Section: Kruskalwallismentioning
confidence: 99%
“…MAPK, Wnt, Notch, JAK-STAT, JNK, NFkB, and PKA signaling pathways all have intrinsic links to epigenetic regulation. 12,13 Current evidence indicates that such regulation may be critical. EZH2, the primary histone methyltransferase for H3K27, is phosphorylated by AKT and CDK1/CDK2 at serine 21, threonine 345 (threonine 350 in humans), and threonine 487 (threonine 492 in humans).…”
Section: Introductionmentioning
confidence: 99%